2022
DOI: 10.1075/lab.21017.arc
|View full text |Cite
|
Sign up to set email alerts
|

Phonological parsing via an integrated I-language

Abstract: Schwartz and Sprouse (2021) argue against property-by-property Transfer (Westergaard, 2021a, b) and for wholesale transfer (Rothman, 2015) into a third language grammar by questioning the cognitive plausibility of “extracting a proper subpart from the … grammar and using that proper sub-system as the basis for a new cognitive state.” I will argue that the insights from the approaches of López (2020); Lightfoot (2020); Dresher (2018), and Westergaard (2021a) when applied to empirical data from L3 English data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Another strength of the current theoretical framework is that the PR analysis is not limited to Mandarin and English, but it can be applied to various languages. The PR is based on MCS which posits that the contrastive feature hierarchy is universal (not the features or the feature order) (Dresher 2018); hence, contrastive hierarchy models like PR can be utilized to various L2 or L3 acquisition contexts (e.g., Natvig 2017;Kwon 2021;Archibald 2022a;2022b). This study has demonstrated how PR can be applied to Mandarin and English vowels and accounts for Mandarin learners' perceptual confusions.…”
Section: A Phonological Window Into L2 Perceptionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another strength of the current theoretical framework is that the PR analysis is not limited to Mandarin and English, but it can be applied to various languages. The PR is based on MCS which posits that the contrastive feature hierarchy is universal (not the features or the feature order) (Dresher 2018); hence, contrastive hierarchy models like PR can be utilized to various L2 or L3 acquisition contexts (e.g., Natvig 2017;Kwon 2021;Archibald 2022a;2022b). This study has demonstrated how PR can be applied to Mandarin and English vowels and accounts for Mandarin learners' perceptual confusions.…”
Section: A Phonological Window Into L2 Perceptionmentioning
confidence: 97%
“…In order to understand the underlying mechanism of perception, it is crucial to recognize how L1 phonology influences L2 perception. As remarked upon above, acquisition of L2 sounds can be constrained considerably due to the learner already possessing robust linguistic resources established in the L1 grammar (Archibald 2022a;2022b;Brown 2000). Nevertheless, our approach to sound learning is akin to that referenced in Flege (1995), Flege and Bohn (2021), and more broadly in White (1988), namely that the mechanisms responsible for L1 acquisition can be applied to L2 acquisition as well because this system stays intact and evolves throughout the lifespan.…”
Section: Phonological-phonetic Representation Modelmentioning
confidence: 99%
“…Benrabah (1991) reports that in the speech of Arabic learners of English, consonants are transferred from Arabic, while vowels form French, and this is due to the respective similarity of these subsystems. Archibald (2022) shows that stress patterns follow a mixture of influence from Arabic and French. He claims that the data he gathered can be explained by adopting a contrastive feature hierarchy model which can formally capture linguistic proximity.…”
Section: Introductionmentioning
confidence: 99%